Case report: Autoimmune nodopathy with concurrent serum and CSF IgG4 anti-neurofascin 155 antibodies - Wang, Wanyu; Liu, Lingchun; Zhang, Mingzhi; Yang, Ruihan; Liu, Da; Yang, Shunyu; Meng, Qiang (Frontiers in Immunology, 2022)
Objective To report a case of autoimmune nodopathy (AN) with concurrent serum and CSF immunoglobulin (Ig)G4 anti-neurofascin 155 (NF155) and anti-GD1b antibodies. Methods A 20-year-old male presented distal weakness of the 4 limbs, hypoesthesia, absent tendon reflexes and sensory ataxia. Nerve conduction studies (NCS), MRI, and autoantibody tests were performed. Results NCS revealed a diffuse demyelinating neuropathy in the peripheral nerve with motor and sensory involvement. MRI of the cervical and lumbar plexus showed diffuse enlargement. IgG4 anti-NF155 antibodies in both serum and CSF and IgG anti-GD1b antibodies in serum were positive. After treatment with IVIg, rituximab, and plasma exchange, the titer of the patient’s anti-NF155 antibodies decreased, but symptoms did not significantly improve. Discussion This patient presented a typical clinical feature of AN with serum and CSF anti-NF155 antibodies and serum anti-GD1b antibodies coexistent but poor response to IVIg, rituximab and plasma exchange. Early detection of antibodies may be helpful in both diagnosis and therapy of the disease. And prospective studies are necessary to demonstrate the potential role of anti-NF155 antibodies in CSF and help further understand this complex and heterogeneous disease.